A new method of determining the change in position of teeth in orthodontic treatment - E. Y. Nikolaeva; T. O. Zubareva; A. G. Dolidze (Кубанский научный медицинский вестник, 2014)
Anomalies position of individual teeth are quite common pathology dentition. This is a problem as during the orthodontic treatment of anomalies and deformations dental system in the preparation of oral prosthetics. Study of literature has shown that the problem of optimal control methods leveling of the teeth was not enough emphasis. Lack of data on the limits of orthodontic treatment for this pathology. The proposed technique will allow us to justify the change in the position of the teeth during orthodontic treatment and get the rules that will continue to guide features orthodontic treatment of patients with abnormalities of the teeth using braces and microimplants.